2017
DOI: 10.1186/s13052-017-0392-6
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in infants: antibodies to deamidated gliadin peptide come first!

Abstract: BackgroundThe onset of coeliac disease (CD) in the first year of life is uncommon and the diagnosis can be challenging due to the suboptimal sensitivity of tissue transglutaminase antibodies (tTG) at this age and the many other possible causes of malabsorption in infants. Antibodies to deamidated gliadin peptides (anti-DGPs), especially IgG, may appear earlier than IgA anti-tTG in very young children with CD.Case presentationWe report here on an 8-month-old child who was evaluated for failure to thrive, consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 55 publications
1
15
0
1
Order By: Relevance
“…The breakdown of 4 years of age was mainly based on the first quartile of age in the entire cohort. This was also within the range of age breakdown between 2 and 7 years in several previous studies [ 15 16 17 18 19 ]. 2) T1DM and non-T1DM groups: Patients were classified into the T1DM group if the diagnosis was reported in the patients' records by their endocrinologists based on standard criteria at the time of the initial serological tests.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…The breakdown of 4 years of age was mainly based on the first quartile of age in the entire cohort. This was also within the range of age breakdown between 2 and 7 years in several previous studies [ 15 16 17 18 19 ]. 2) T1DM and non-T1DM groups: Patients were classified into the T1DM group if the diagnosis was reported in the patients' records by their endocrinologists based on standard criteria at the time of the initial serological tests.…”
Section: Methodssupporting
confidence: 88%
“…Although TTG IgA is the obligatory test for correlation with histology and for screening at risk populations for CD in the presence of IgA sufficiency, there is a debate whether TTG IgA is a reliable test in younger children, given concerns about age-related changes in immunogenicity [ 15 16 ]. We showed that mean TTG IgA in the <4.0 years of age group was slightly but significantly lower than the ≥4.0 years of age group when analyzed in a normal non-CD cohort, suggesting there was an age-related difference in TTG IgA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the regional genetic diversity of the human population and the nutritional characteristics observed in different countries, differences in the prevalence of celiac disease are due to the use of diagnostic tests with unequal specificity and sensitivity [17,18,19]. A retrospective study of blood samples from adult Americans taken in 1974, 1989, and 2001 showed that the incidence of serological markers of celiac disease in 1974 was 1:501, in 1989 -1:219, and in 2001 -1:105.…”
Section: Reviews обзорыmentioning
confidence: 99%
“…7 ,8 Several studies have suggested a protective role of breastfeeding and/or the timing and quantity of gluten introduction in the subsequent development of celiac disease. Especially, prolonged breastfeeding during the introduction of gluten-containing feeding has been associated with a reduced risk of developing celiac disease in infancy 9,10 . The mentioned results suggest the existence of a 'window of opportunity' between 4 and 6 months of age in which gluten can be introduced in small amounts 11 .…”
mentioning
confidence: 99%